Bertil Johansson: Law and lawyers in Elizabethan England as evidenced tn the plays of Ben ]onson and Thomas Middleton. Stockholm. (Lund), Almqvist & Wiksell, (1967). 65 p. 28 x 15 cm. (Acta Universitatis Stockholmiensis. Studies in English, 18). - Allende, Nora A. de (Universidad Nacional de Cuyo. Facultad de Filosofía y Letras. Instituto de Literaturas Modernas, 1969)

(untitled)
Fil: Allende, Nora A. de. Universidad Nacional de Cuyo